Reassembling Democracy Ritual as Cultural Resource - Houseman, Michael; Salomonsen, Jone (Bloomsbury Academic, 2020)
Diverse processes of democratic participation - and exclusion - are closely bound by ritual acts and complexes. This collection is the result of collaborations and conversations between international researchers who have focused on the use of those cultural resources identifiable as "ritual" as they reassemble democracy. The main question integrating the collection concerns the ways in which the performative qualities of ritual resources achieve their potential as forms of personal and political empowerment in our changing and challenging world.